SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PESERTA KOMPETISI SAINS MADRASAH DI MA MUALLIMAT NW ANJANI DENGAN METODE TOPSIS BERBASIS WEB - Lalu Puji Indra Kharisma; Rabiatul Adawiyah; Yudi Sutaryana (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2024)
Decision Support System (SPK) is a computer-based information system that produces various alternative decisions to assist in handling a structured or unstructured problem. At MA Muallimat NW Anjani, the selection of prospective KSM participants is still done manually, where often students who are selected as madrasah representatives are chosen by surprise, so that often the students who are appointed are less prepared, and if the selection is done manually through data collection it will take a long time. Decision Support System for the selection of KSM candidates at MA Muallimat NW Anjani with the web-based Topsis method and its software development method using the Prototype Method which begins with gathering needs, designing prototypes, evaluating prototypes, coding systems, testing systems, evaluating systems and implementing systems. This decision support system performs calculations from Olympic subject scores, Olympic attendance, Olympic experience scores and Olympic test scores and successfully provides suitable recommendations based on the selection results. In this application, the admin and Head of Madrasah can print the selection results to be distributed to students or students can see the selection results on the web page. Keywords: Decision Support System, TOPSIS, KSM, Prototype.